2018
DOI: 10.1186/s13018-018-0912-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hyperlipidemia on rotator cuff diseases: a systematic review

Abstract: BackgroundRotator cuff disease is a common condition that causes shoulder pain and functional disability. Recent studies suggested that hyperlipidemia might be associated with the development of rotator cuff disease. The objective of this study was to explore the relationship of hyperlipidemia and rotator cuff diseases.MethodsA computerized search using relevant search terms was performed in the PubMed, EMBASE, and Cochrane Library databases, as well as a manual search of reference and citation lists of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 45 publications
0
33
0
1
Order By: Relevance
“…47 A further ICON consensus statement highlighted that patient characteristics relating to general health may be a major confounder to treatment outcomes in tendinopathy. 48 Patients with chronic tendinopathy, especially older and more sedentary individuals, often have associated comorbidities, for example, diabetes, 49 high cholesterol 50 and high body mass index. 51 These characteristics are not routinely measured in tendinopathy studies, but it is recommended that they are reported in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…47 A further ICON consensus statement highlighted that patient characteristics relating to general health may be a major confounder to treatment outcomes in tendinopathy. 48 Patients with chronic tendinopathy, especially older and more sedentary individuals, often have associated comorbidities, for example, diabetes, 49 high cholesterol 50 and high body mass index. 51 These characteristics are not routinely measured in tendinopathy studies, but it is recommended that they are reported in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally assumed that localized chitosan binds to cholesterol, thus lowering the retear rate, but further work is needed to confirm this assumption. 22,28,34,48…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] According to previous findings, mechanical properties of tendons are affected by lipids that pile up within the extracellular matrix when an individual develops hyperlipidemia. [ 14 , 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Hyperlipidemia is one of the extrinsic factors that have been adversely associated with tendinopathy [ 12 ] and its treatment. [ 13 ] Associations of hyperlipidemia with CT have been described elsewhere [ 14 ] but not in Taiwan.…”
Section: Introductionmentioning
confidence: 99%